Leptin is a potential biomarker of childhood obesity and an indicator of the effectiveness of weight‐loss interventions - Mohammad Al Zein (20090700) (2024)
Childhood obesity represents a significant public health concern, imposing a substantial burden on the healthcare system. Furthermore, weight‐loss programs often exhibit reduced effectiveness in adults who have a history of childhood obesity. Therefore, early intervention against childhood obesity is imperative. Presently, the primary method for diagnosing childhood obesity relies on body mass index (BMI), yet this approach has inherent limitations. Leptin, a satiety hormone produced by adipocytes, holds promise as a superior tool for predicting both childhood and subsequent adulthood obesity. In this review, we elucidate the tools employed for assessing obesity in children, delve into the biological functions of leptin, and examine the factors governing its expression. Additionally, we discuss maternal and infantile leptin levels as predictors of childhood obesity. By exploring the relationship between leptin levels and weight loss, we present leptin as a potential indicator of the effectiveness of obesity interventions. Other Information Published in: Obesity Reviews License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1111/obr.13807